Isochlorogenic acid derived from stevia improves antioxidant capacity, immune function and intestinal microbiota in weaned piglets - Wang, Yuxin; Luo, Yong; Zou, Honglei; Gao, Wei; Yu, Bing; He, Jun; Song, Weiguang; Luo, Yuheng; Zheng, Ping; Mao, Xiangbing; Xuan, Yueqi; Xu, Meili; et al. (Frontiers in Veterinary Science, 2025)
Isochlorogenic acid (ICGA), a phenolic compound with demonstrated antioxidant, antibacterial, and anti-inflammatory properties, is widely present in plants. This study investigated the effects of dietary ICGA supplementation on growth performance, diarrhea incidence, antioxidant status, immune function, and intestinal microbiota in weaned piglets. A total of 180 crossbred piglets (Duroc × Landrace × Yorkshire) with an average initial body weight of 6.77 ± 0.18 kg were randomly allocated to five dietary treatments based on gender and weight. The diets consisted of a basal formulation supplemented with 0 (CON), 100, 200, 400, or 800 mg/kg ICGA for 28 days. Each treatment comprised six replicates, with six piglets per pen. Supplementation with 200 mg/kg ICGA significantly increased the average daily gain (ADG) by 3.49% during days 15–28 compared to the CON group (p < 0.05). Furthermore, diets containing 200 and 400 mg/kg ICGA improved the apparent total tract digestibility (ATTD) of dry matter (by 1.84 and 1.54%), crude protein (by 4.48 and 4.39%), gross energy (by 3.01 and 2.99%), ether extract (by 23.18 and 17.49%), and ash (by 8.80 and 5.13%) (p < 0.01). On day 14, serum catalase (CAT) activity increased by 47.78% in the 400 mg/kg group (p < 0.05), and this increase reached 77.65% by day 28 (p < 0.05). Meanwhile, the 200 mg/kg group exhibited a 75.78% elevation in total antioxidant capacity (T-AOC) on day 28 (p < 0.05). Serum immunoglobulin levels were also enhanced; 200 and 400 mg/kg ICGA up-regulated IgA by 23.77 and 33.42%, and IgM by 18.81 and 30.86% on day 14 (p < 0.01). Microbiota analysis indicated that ICGA supplementation increased the abundance of beneficial Bacteroidota and Prevotella, while reducing pathogenic taxa such as Peptostreptococcaceae, Proteobacteria, and Staphylococcus. In conclusion, dietary ICGA at 200–400 mg/kg effectively reduced diarrhea incidence, enhanced nutrient digestibility, improved antioxidant capacity, strengthened humoral immunity, and positively modulated gut microbiota in weaned piglets. Further research is warranted to elucidate the underlying mechanisms and assess the potential for practical application in swine production.